Chemokine signaling links cell-cycle progression and cilia formation for left–right symmetry breaking - Liu, Jingwen; Zhu, Chengke; Ning, Guozhu; Yang, Liping; Cao, Yu; Huang, Sizhou; Wang, Qiang (PLOS Biology, 2019)
During left-right symmetry breaking in zebrafish, proliferation defects of dorsal forerunner cells are often accompanied by impaired cilia elongation in Kupffer’s vesicle. This study shows that Cxcr4a signaling promotes the activity of Cyclin D1-CDK4/6, which accelerates the G1/S transition in dorsal forerunner cells and then facilitates cilia formation via stabilization of Foxj1a.